2018
DOI: 10.1093/femsec/fiy158
|View full text |Cite
|
Sign up to set email alerts
|

Southern South Australian groundwater microbe diversity

Abstract: Groundwater is increasingly used globally for domestic, industrial and agricultural production. While many studies have focused on groundwater as a resource, the diverse ecosystems within are often ignored. Here, we assess 54 Southern South Australian groundwater microbial communities from the populated part of the state to assess their status and dynamics in isolated groundwater systems. We observed a strong site-to-site individuality in groundwater bacterial communities, likely due to the isolated nature of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 56 publications
2
6
0
Order By: Relevance
“…More specifically, we were interested in examining if there is an abrupt change in community composition at a certain point of the land use‐induced contamination gradient, using nitrate‐N concentration as a surrogate. Our results showed that despite different environmental settings in agricultural vs. urban springs, bacterial communities in these two types of human‐disturbed springs were indistinguishable: they both differed strongly from unimpacted reference springs, and converged independently towards a shared ‘pollutant community’ ( sensu Smith et al ., 2018). This result suggests that, although the specific stressors in urban and agriculturally disturbed sites must be different (e.g., fertilization vs. organic pollutants), NO 3 − ‐N concentration of the spring water is an appropriate surrogate for groundwater quality, because it effectively encapsulates similar trends in several other water quality parameters (e.g., conductivity, DOC, tot‐P).…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, we were interested in examining if there is an abrupt change in community composition at a certain point of the land use‐induced contamination gradient, using nitrate‐N concentration as a surrogate. Our results showed that despite different environmental settings in agricultural vs. urban springs, bacterial communities in these two types of human‐disturbed springs were indistinguishable: they both differed strongly from unimpacted reference springs, and converged independently towards a shared ‘pollutant community’ ( sensu Smith et al ., 2018). This result suggests that, although the specific stressors in urban and agriculturally disturbed sites must be different (e.g., fertilization vs. organic pollutants), NO 3 − ‐N concentration of the spring water is an appropriate surrogate for groundwater quality, because it effectively encapsulates similar trends in several other water quality parameters (e.g., conductivity, DOC, tot‐P).…”
Section: Discussionmentioning
confidence: 99%
“…A dominance of Proteobacteria was regularly reported ( Shi et al, 1999 ; Detmers et al, 2004 ; Hendrickx et al, 2005 ; Boyd et al, 2007 ; Griebler and Lueders, 2009 ; Flynn et al, 2012 ; Gregory et al, 2014 ; Sirisena et al, 2018 ). Besides Proteobacteria, Actinobacteria , Firmicutes , Bacteriodetes , and Nitrospirae have frequently been detected at relevant abundances ( Hendrickx et al, 2005 ; Griebler and Lueders, 2009 ; Zhou et al, 2012 ; Navarro-Noya et al, 2013 ; Gregory et al, 2014 ; Nowak et al, 2017 ; Bellini et al, 2018 ; Savio et al, 2018 ; Smith et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…We are only beginning to understand whether and how energy-diversity relationships known from macroecology apply to complex natural bacterial communities. In fact, there is a growing body of evidence that diversity-productivity relationships also rule microbial communities (Smith, 2007).…”
Section: Link Between Dom Diversity and Microbial Community Compositionmentioning
confidence: 99%
“…THE enumeration of bacteria from any environment increases our knowledge of microbial dynamics and develops a deepened understanding of conditions and factors that favor the growth of individual species. Shifts in abundance of bacterial species in dynamic systems have been demonstrated in several biological and ecological environments, including human gut microflora (1,2), groundwater (3)(4)(5), oceanic (6,7), and food-related environments (8)(9)(10)(11). From these studies, the importance of bacterial diversity is linked to the overall health of those environments.…”
mentioning
confidence: 99%
“…Flow cytometry is currently used to determine microbial abundances in a range of environmental, medical, and industrial environments (5,(13)(14)(15)(16). In wine, enumerating yeast and lactic acid bacteria during fermentation is crucial for understanding the dynamics of successful and efficient wine production.…”
mentioning
confidence: 99%